Implementation of the Talking Stick Model as an Effort to Improve Islamic Education Learning Outcomes in Elementary Schools - Erfina Murliati; Zubaidah Zubaidah (Jurnal Indonesia Pendidikan Profesi Guru, 2025)
Objective: Islamic Education in elementary schools still uses a classical model, which results in students being less active, not independent, and many failing to achieve the Minimum Mastery Criteria (KKM). Objective: This study aims to examine the implementation of the Talking Stick learning model in improving Islamic Education learning outcomes for students at SD Negeri 95 Bengkulu Selatan. Method: The method used in this study is Classroom Action Research, which consists of four stages: planning, acting, observing, and reflecting. Results: There was a significant improvement in student learning outcomes. In the pre-cycle, the average student score was 65.7 with a mastery percentage of 40%. In Cycle I, the average score increased to 73.1 with a mastery percentage of 55%. In Cycle II, the average score increased further to 83, with a mastery percentage of 90%, indicating that the Talking Stick model is effective in improving student learning outcomes. Conclusion: The application of the Talking Stick model in Islamic Education at SD Negeri 95 Bengkulu Selatan successfully improved student learning outcomes. This improvement is reflected in the increased average scores and mastery percentage, which reached 90% in Cycle II, surpassing the established KKM. Contribution: This study contributes by offering a more effective alternative learning model, namely the Talking Stick model, which teachers can use to enhance students’ active participation, motivation, and learning outcomes in Islamic Education. It is also expected to provide insights for teachers to use more interactive and enjoyable learning models in the classroom.